Possibilities of CoDeSys Programming System during Software Development and Designing of Micro-Processor Control Systems - S. O. Novikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A great attention is presently paid to technologies pertaining to software development for systems which are applied for control of industrial automatic equipment designed on the basis of programmable logical controllers (PLC) and practical programming using languages of International Electrotechnical Commission (IEC) 61131-3 standard.A programming CoDeSys complex is one of the systems for PLC software development. This complex has been developed by 3S-Smart Software Solutions GmbH (3S) company. Its main purpose is to program PLC and industrial computers in accordance with the IEC 61131-3 standard. A number of unordinary 3S solutions have led to the fact that the CoDeSys is considered now as a standard PLC programming tool of the leading European manufacturers: ABB, Beckhoff, Beck IPC, Berger Lahr, Bosch Rexroth, ifm, Keb, Kontron, Lenze, Moeller, WAGO, Fastwel и др.An introduction of the standard has served as a foundation for creation of the unified school for specialists’ training. A person who is trained in accordance with the program including the IEC 61131-3 standard shall be able to work with PLC of any company. At the same time if he/she has had some experience of work with any PLC then his/her skills shall be helpful and significantly simplify studying process of new possibilities.